Wish You Were Here; A Short History of New Zealand Muslims and Integration - Abdullah Drury (Nazhruna: Jurnal Pendidikan Islam, 2020)
The recent court case of the Australian terrorist responsible for murdering 51 worshippers inside two mosques in Christchurch, New Zealand, has focused attention on this South Pacific nation. Nation-building, with its inherent practices of inclusion and exclusion into the social hierarchy, began here in the nineteenth century and accelerated throughout the twentieth century. History of Muslims in New Zealand, or New Zealand Islam, is a rich narrative illustrative of tendencies and biases that are both common to, as well as divergent from, patterns elsewhere in the English speaking world and Western societies in general. The integration of Muslim immigrants and refugees, and converts to Islam, into this complex social bricolage, however, has been challenging and at times convoluted. This essay will support us to consider why and how this is the case.